Lord of the flies - Golding, William, 1911-1993. (Old Greenwich, CT : Listening Library, 1984)
The Cliffhanger technique encourages students to read along with the cassette just far enough to really grab their interest, then the narrator stops.
For junior high students.
Keywords: Airplane crash survival -- Juvenile fiction; Shipwreck survival -- Juvenile fiction; Survival -- Juvenile fiction; Survival at sea -- Juvenile fiction; Political anthropology -- Juvenile fiction; Primitive societies -- Juvenile fiction